Cediranib combined with carboplatin and paclitaxel in patients with metastatic or recurrent cervical cancer (CIRCCa): a randomised, double-blind, placebo-controlled phase 2 trial. Issue 15 (November 2015) - Symonds, R Paul; Gourley, Charlie; Davidson, Susan; Carty, Karen; McCartney, Elaine; Rai, Debbie; Banerjee, Susana; Jackson, David; Lord, Rosemary; McCormack, Mary; Hudson, Emma; Reed, Nicholas; et al.
Summary: Background: Patients treated with standard chemotherapy for metastatic or relapsed cervical cancer respond poorly to conventional chemotherapy (response achieved in 20–30% of patients) with an overall survival of less than 1 year. High tumour angiogenesis and high concentrations of intratumoural VEGF are adverse prognostic features. Cediranib is a potent tyrosine kinase inhibitor of VEGFR1, 2, and 3. In this trial, we aimed to assess the effect of the addition of cediranib to carboplatin and paclitaxel chemotherapy in patients with metastatic or recurrent cervical cancer. Methods: In this randomised, double-blind, placebo-controlled phase 2 trial, which was done in 17 UK cancer treatment centres, patients aged 18 years or older initially diagnosed with metastatic carcinoma or who subsequently developed metastatic disease or local pelvic recurrence after radical treatment that was not amenable to exenterative surgery were recruited. Eligible patients received carboplatin AUC of 5 plus paclitaxel 175 mg/m 2 by infusion every 3 weeks for a maximum of six cycles and were randomised centrally (1:1) through a minimisation approach to receive cediranib 20 mg or placebo orally once daily until disease progression. The stratification factors were disease site, disease-free survival after primary therapy or primary stage IVb disease, number of lines of previous treatment, Eastern Cooperative Oncology Group performance status, and investigational site. All patients, investigators, and trial personnel were masked to study drug allocation. The primary endpoint was progression-free survival. Efficacy analysis was by intention to treat, and the safety analysis included all patients who received at least one dose of study drug. This trial is registered with the ISCRTN registry, number ISRCTN23516549, and has been completed. Findings: Between Aug 19, 2010, and July 27, 2012, 69 patients were enrolled and randomly assigned to cediranib (n=34) or placebo (n=35). After a median follow-up of 24·2 months (IQR 21·9–29·5), progression-free survival was longer in the cediranib group (median 8·1 months [80% CI 7·4–8·8]) than in the placebo group (6·7 months [6·2–7·2]), with a hazard ratio (HR) of 0·58 (80% CI 0·40–0·85; one-sided p=0·032). Grade 3 or worse adverse events that occurred in the concurrent chemotherapy and trial drug period in more than 10% of patients were diarrhoea (five [16%] of 32 patients in the cediranib group vs one [3%] of 35 patients in the placebo group), fatigue (four [13%] vs two [6%]), leucopenia (five [16%] vs three [9%]), neutropenia (10 [31%] vs four [11%]), and febrile neutropenia (five [16%] vs none). The incidence of grade 2–3 hypertension was higher in the cediranib group than in the control group (11 [34%] vs four [11%]). Serious adverse events occurred in 18 patients in the placebo group and 19 patients in the cediranib group. Interpretation: Cediranib has significant efficacy when added to carboplatin and paclitaxel in the treatment of metastatic or recurrent cervical cancer. This finding was accompanied by an increase in toxic effects (mainly diarrhoea, hypertension, and febrile neutropenia). Funding: Cancer Research UK and AstraZeneca.